Produk Metabolisme Rumen pada Sapi Perah Laktasi - S.N.O. Suwandyastuti; Efka Aris Rimbawanto (Jurnal Agripet, 2015)
(Rumen metabolism product on lactating dairy cattle)ABSTRACT. The rumen microorganism, as yeast, have an important role in rumen fermentation processes and the rumen metabolism product. A research had been done to study the use of yeast, Saccharomyces cereviseae in Lactating dairy cattle ration. The research had been conducted by experimental method, in a Latin Square Design. The animal were subjected as column and periods function as row. The treatment to be tested were four levels of yeast addition, namely : 0, 5, 10 and 15 g/cattle/day. The variables measured were rumen metabolism product : Total Volatile Fatty Acids (T-VFA), Acetate (C2), Propionate (C3), Butyrate (C4), Formiate, Valerate, Nitrogen Ammonia and C2/C3. Based on the all variables measured, it was indicated that the addition of yeast Saccharomyces cereviseae up to 15 g/cattle/day have not changed the rumen metabolism product on lactating dairy cattle; although it was a normally production of total VFA (96,86 9,94 mM/L and C2/C3 (3,08 0,14), but it was very high production of N-NH3 (12,85 2,72 mM/L). To increase the efficiency of metabolism processes, it is need the addition of fermentable carbohydrate in ration.